Utilization of Imperfect Produce of Honey Guava to Improving the Economy and Welfare of Farmers - Mahyuni, Eka Lestari; Aritonang, Evawany Yunita; Soeparno, Wahyu Sugeng Imam (Journal of Saintech Transfer, 2023)
Huney guava (Syzygium aqueum) is a potential agricultural product of Secanggang District, Langkat Regency, which is generally sold in fresh fruits. The production of Guava in this area reaches 150 kg per farmer, with 25-30 kg of them remain unsold. This community service aims to disseminate knowledge and technology to farmers about processing honey guava fruit into chips with the trade name "KeJaM". This activity is expected to be a solution for farmers in processing unsold products into new products that can increase economic value, as well as reduce agricultural waste. In this activity, the community service activities team also provided honey herb processing equipment, namely a vacuum fryer and spinner, so that the honey guava chips produced still have the characteristic honey guava taste. KeJaM is a healthy snack which is expected to attract the interest of public in order to improve the economy and welfare of farmers.